Conhecimento, atitude e prática de mulheres com câncer de mama sobre os métodos de detecção precoce - Gomes, Altamira Mendonça Félix (2016)
Early detection of breast cancer actions are increasingly necessary in order to achieve the reduction of morbidity and mortality caused by this. Among these actions are the incentive to carry out the clinical breast exam and mammography. When this cancer is detected in its earliest form the patient is subjected to more aggressive and harmful treatments. Poor knowledge of the population in relation to these aspects ultimately makes it more prone to non-adoption of secondary prevention practices of breast cancer and the population turns out to have the disease at more advanced stages. In the quest for understanding on these aspects, this research aims to assess the knowledge, attitude and practice of women with breast cancer on screening methods (clinical breast exam and mammography). This is a cross-sectional study associated with the CAP survey conducted in women with breast cancer undergoing chemotherapy met by a referral center for oncology in the city of Fortaleza, Ceará. The sample consisted of 108 women who were asked to sign the consent form and answer questionnaires sociodemographic, gynecologic, obstetric and clinical as well as the Survey CAP in November 2015 to March 2016. All data were tabulated and analyzed using version 20.0 of the Statistical Package for Social Sciences (SPSS). The aspects of Resolution 466 ̸ 2012 National Health Council were respected. The results showed that the knowledge and practice of women with regard to screening tests were inadequate among most participants. The approach was considered appropriate in most of the sample. Deficiency of knowledge was the contribution of the misconception that screening tests can prevent breast cancer. The evaluation of the practice presented frequency of inadequate achievement with respect to the two exams, with many participants carrying out the practice only once, where she was diagnosed the disease. Statistical significance was found between age and religion with inadequate practice, between the time of breastfeeding and age at menarche and inadequate knowledge and inappropriate practice with how often held mammography. More educational activities focused on the needs of women with breast cancer in relation to early detection of the disease are essential.